Eccrine Porocarcinoma: New Insights and a Systematic Review of the Literature. Issue 10 (October 2018) - Nazemi, Azadeh; Higgins, Shauna; Swift, Reyna; In, Gino; Miller, Kimberly; Wysong, Ashley
Abstract : BACKGROUND: Eccrine porocarcinoma (EPC) is a rare cutaneous neoplasm with high potential for morbidity and mortality. Due to its rarity, there is a paucity of data profiling diagnosis, work-up, and management. OBJECTIVE: To consolidate reported information on demographics, diagnostics, clinical behavior, treatment modalities, and patient outcomes in EPC to provide a reference tool to optimize diagnosis and management. METHODS: A comprehensive PubMed search was performed from 1963 to November 2017 using PRISMA guidelines. This yielded 155 articles detailing 206 cases of porocarcinoma. RESULTS: Eccrine porocarcinoma most often presents in elderly patients on the head and neck or lower limbs. Metastatic disease at presentation is not uncommon (22%). Primary tumor location is significantly correlated with presence of metastasis ( p = .038). The most common treatment is excision followed by Mohs micrographic surgery (MMS), although the outcomes after MMS were superior to those after surgical excision. CONCLUSION: This systematic review of individual patient data reveals that all patients should have a histological diagnosis with imaging considered for high-risk cases. Primary tumor location should also be considered in diagnostic and therapeutic decision-making. Although wide local excision (WLE) is currently the first-line treatment, MMS is becoming increasingly used, with evidence indicating improved outcomes as compared to those seen with WLE.